163k views
5 votes
(m-3)/(7)=(m)/(m+8) Solve the proportion.

1 Answer

1 vote

Answer: m=6, m=-4

Explanation:

To solve this proportion, we have to cross multiply.


(m-3)/(7) =(m)/(m+8)


(m-3)(m+8)=7m

Now that we have cross multiplied, we actually need to FOIL the left side to expand the equation.


m^2+8m-3m-24=7m

Combine like terms.


m^2+5m-24=7m

We can move all terms to one side and then solve for m.


m^2-2m-24=0

We can actually factor this to:


(m-6)(m+4)=0

We set each factor equal to 0 to find m.

m-6=0

m=6

m+4=0

m=-4

User Damien McGivern
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.